Sport Financing Systems in Austria and Poland: A Legal and Economic Perspective - Waśkiewicz, Zbigniew (PRAWO i WIĘŹ, 2025)
This paper presents a comparative analysis of the sports financing systems in Austria and Poland from legal and economic perspectives. Austria employs a centralised model of sports funding, primarily based on the Federal Sports Promotion Act of 2017, which mandates an annual contribution of at least €120 million from gambling revenues, administered by the Bundes-Sportförderungsfonds. In contrast, Poland operates under a decentralised model, with local governments responsible for around 75% of public sports expenditure, supplemented by substantial support from state-owned enterprises. Both countries utilise public-private partnerships (PPPs), sponsorship and targeted tax incentives, albeit with varying degrees of institutionalisation. While Austria benefits from stable institutional funding, it risks stagnation in innovation and accountability. Meanwhile, Poland’s dynamic but fragmented model leads to regional disparities and challenges in strategic coordination. Recommendations include introducing performance-based funding reforms in Austria and developing a national sports financing strategy in Poland.